2017
DOI: 10.7554/elife.25492
|View full text |Cite
|
Sign up to set email alerts
|

Co-agonists differentially tune GluN2B-NMDA receptor trafficking at hippocampal synapses

Abstract: The subunit composition of synaptic NMDA receptors (NMDAR), such as the relative content of GluN2A- and GluN2B-containing receptors, greatly influences the glutamate synaptic transmission. Receptor co-agonists, glycine and D-serine, have intriguingly emerged as potential regulators of the receptor trafficking in addition to their requirement for its activation. Using a combination of single-molecule imaging, biochemistry and electrophysiology, we show that glycine and D-serine relative availability at rat hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 57 publications
6
97
0
Order By: Relevance
“…Therefore, detecting and measuring D-serine levels has become necessary in several subfields of neuroscience and other disciplines but has proven technically challenging. In the brain and spinal cord, assessing the occupancy of the NMDAR co-agonist binding site is an excellent first approach to assess D-serine levels (Papouin et al ., 2012; Papouin et al ., 2017b; Ferreira et al ., 2017). However, major limitations of this approach are that 1) it provides little quantitative insights into the actual concentration of D-serine, 2) it is subject to a strong ceiling effect (once the co-agonist binding site is saturated, higher levels of D-serine go undetected), 3) glycine can also bind to the NMDAR co-agonist binding site and compete with D-serine, 4) this approach is subject to changes and differences in the affinity of the NMDAR co-agonist binding site, and finally 5) this method is only useful in conditions where recording NMDAR activity is technically possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, detecting and measuring D-serine levels has become necessary in several subfields of neuroscience and other disciplines but has proven technically challenging. In the brain and spinal cord, assessing the occupancy of the NMDAR co-agonist binding site is an excellent first approach to assess D-serine levels (Papouin et al ., 2012; Papouin et al ., 2017b; Ferreira et al ., 2017). However, major limitations of this approach are that 1) it provides little quantitative insights into the actual concentration of D-serine, 2) it is subject to a strong ceiling effect (once the co-agonist binding site is saturated, higher levels of D-serine go undetected), 3) glycine can also bind to the NMDAR co-agonist binding site and compete with D-serine, 4) this approach is subject to changes and differences in the affinity of the NMDAR co-agonist binding site, and finally 5) this method is only useful in conditions where recording NMDAR activity is technically possible.…”
Section: Introductionmentioning
confidence: 99%
“…Two methods are currently available. The first one is electrophoresis-based, in particular high performance liquid chromatography (Papouin et al ., 2017b) or capillary electrophoresis (Ferreira et al ., 2017) which has been amply documented. While they provide high levels of precision and reliability, they also require expensive equipment and extensive technical expertise.…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed by Dore and colleagues (Dore et al ), the existence and biological relevance of metabotropic NMDAR signaling is an active area of research with several investigators finding both supportive (Yang et al ; Kessels et al ; Nabavi et al ; Tamburri et al ; Dore et al ; Kim et al ; Stein et al ) and contradictory (Babiec et al ; Volianskis et al ; Sanderson et al ) evidence. Among the former, several studies have revealed ion flux‐independent trafficking of GluN2‐containing NMDARs both by NMDAR agonists (Vissel et al ; Barria and Malinow ) and by co‐agonists (Nong et al ; Ferreira et al ). Together, these data add to the rich repertoire by which neuronal communication can be shaped by a growing number of NMDAR modulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although the population of neuronal GluN2A and GluN2B was initially thought to be enriched in the synaptic or extrasynaptic membrane, respectively (Kew et al ; Tovar and Westbrook ; Liu et al ), substantial amounts of extrasynaptic GluN2A and synaptic GluN2B have been identified (Luo et al ; Groc et al ; Thomas et al ; Harris and Pettit ; Petralia et al ), and the relative mobility of these receptor populations are subtype specific, with GluN2B being more mobile than GluN2A (Groc et al ; Ferreira et al ), and GluN2A less rapidly endocytosed than GluN2B (Lavezzari et al ). Thus, synaptic receptor levels are in a state of dynamic equilibrium being routed into and out of the synapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation